A qualified endorsement of embryonic stem cell research, based on two widely shared beliefs about the brain-diseased patients such research might benefit - DiSilvestro, R. (Journal of medical ethics, 2008)
Are there persuasive approaches to embryonic stem cell (ESC) research that appeal, not just to those fellow-citizens in one’s own ideological camp, nor just to those undecided citizens in the middle, but to those citizens on the other side of the issue? I believe that there are such arguments and in this short paper I try to develop one of them. In particular, I argue that certain beliefs shared by some proponents and some opponents of ESC research—beliefs about the personal identity and moral status of those who are victims of terrible brain diseases—are beliefs that should lead us to adopt a qualified endorsement of ESC research.